THE EFFECTIVENESS OF THE PAYROLL ACCOUNTING SYSTEM ON INTERNAL CONTROL OF EMPLOYEE SALARY PAYMENTS (CASE STUDY AT BPKAD WEST JAVA PROVINCE) - Senita Ardiya Ramadini; Yati Mulyati (Jurnal Ekonomi, 2023)
This study aims to determine the effectiveness of the utilization of the payroll accounting system on internal control of employee salary payments at BPKAD West Java Province, in helping to manage payments and calculations of employee salaries in the current month and budget estimates for the following year. BPKAD or the Regional Financial and Asset Management Agency acts as the Regional General Treasurer (BUD) in managing regional finances and assets in the supporting affairs of the Regional Government. BPKAD oversees 38 Regional Work Units (SKPD) within West Java Province. This type of research is quantitative research. The population used is the salary managers in each BPKAD of West Java Province. A total of 100 samples were used as a sampling technique in this study using purposive sampling. Primary data is used as a data source which will be obtained through distributing questionnaires to respondents. Data analysis in this study used the help of the SPSS version 23.0 program by conducting descriptive analysis tests, data quality tests, classical assumption tests, and hypothesis testing. The results of the study prove that payroll accounting implemented in the agency is in accordance with the payroll accounting standards applicable in Indonesia. This is evidenced by the results of the study showing that the payroll accounting system has a positive and significant effect on internal control at BPKAD West Java Province. In addition, based on the results of the questionnaire distributed through google forms, it proves that with the help of the use of a payroll accounting system, it is able to make internal control in an agency more accurate, timely, effective, and on target.